2015
DOI: 10.1002/celc.201500408
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Tier Hierarchical Clusters of Carbon‐Coated Li4Ti5O12 Single Crystals as High‐Power and High‐Energy Anodes for Lithium‐Ion Batteries

Abstract: A novel three‐tier hierarchical cluster lithium‐ion battery (LIB) anode is reported here, consisting of 1) carbon‐coated Li4Ti5O12 crystals as the first nano‐tier (ca. 10 nm) for high‐rate capability; 2) submicron spheres consisting of Li4Ti5O12 crystals as the second submicron tier (100–300 nm), facilitating electrolyte infiltration and Li+ diffusion; and 3) clusters comprising Li4Ti5O12 spheres as the third micron‐sized tier (1–2 μm) to increase the packing density of active materials for high‐power LIBs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…One is to introduce carbon after the synthesis of Li 4 Ti 5 O 12 , [7,23] and the other is called in situ carbon-coating, i.e., forming a carbon layer during the phase formation of the Li 4 Ti 5 O 12 . There are two primary ways to introduce carbon on the surface of Li 4 Ti 5 O 12 particles.…”
Section: Carbon Surface Modification Of LI 4 Ti 5 O 12mentioning
confidence: 99%
See 3 more Smart Citations
“…One is to introduce carbon after the synthesis of Li 4 Ti 5 O 12 , [7,23] and the other is called in situ carbon-coating, i.e., forming a carbon layer during the phase formation of the Li 4 Ti 5 O 12 . There are two primary ways to introduce carbon on the surface of Li 4 Ti 5 O 12 particles.…”
Section: Carbon Surface Modification Of LI 4 Ti 5 O 12mentioning
confidence: 99%
“…Bai et al [23] reported a typical three-tier hierarchical micro-/submicron-/nano-structured Li 4 Ti 5 O 12 /C cluster in which the nanosized carbon-coated Li 4 Ti 5 O 12 single crystals (ca. Furthermore, hierarchical spherical Li 4 Ti 5 O 12 /C composites can also be realized via a simple organic carbon source thermal pyrolysis process under certain conditions.…”
Section: Morphology Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic carbon from various sources subjected to different pyrolysis shows variable degrees of graphitization. Common organic carbon sources used for Li 4 Ti 5 O 12 include glucose [99][100][101][102][103], sucrose [104][105][106][107], sugar [108,109], starch [110], melamine [111,112], malic acid [113], toluene [114], citric acid [115,116], pitch [117,118], acetonitrile [119], and polymers [120][121][122][123][124][125][126]. The differences, advantages and advanced modification approaches of inorganic and organic carbon are summarized below.…”
Section: Advanced Carbon Sourcesmentioning
confidence: 99%